Defining Diagnostic Criteria for Neurogenic Thoracic Outlet Syndrome: An Expert Consensus. - Wagner, Eric R.; Sullivan, Constance M.; Cuneo, Kevin R.; Chopra, Krishna N.; Omole, Oluwakorede; Gottschalk, Michael B.; Bowers, Robert L. (Orthopaedic Journal of Sports Medicine, 2026)
Background: Neurogenic thoracic outlet syndrome (nTOS) can present itself in a number of ways, often resulting in diagnostic ambiguity. Purpose: To establish a consensus among upper extremity experts using the Delphi method to determine the most clinically relevant criteria in distinguishing nTOS to help create a diagnostic algorithm. Study Design: Consensus statement. Methods: A panel of 20 upper extremity experts rated the importance of 54 different clinical items in reference to distinguishing nTOS. Items were ranked on a scale from 0 (least important) to 10 (most important). The mean and standard deviation for each item's rankings were calculated. The Cronbach alpha (α) value was used to determine the degree of concordance among the panelists' rankings. Analogous items with similarly high rankings were combined to help develop the final criteria. Results: A Cronbach α value of.936 was calculated, indicating a high degree of consensus among the experts' responses. Similar items with higher rankings were combined to help develop the final criteria. The 5 criteria deemed clinically important for nTOS were (1) a positive response to injections (pectoralis minor, anterior scalene, middle scalene); (2) upper or lower trunk radiating symptoms that worsen with supraclavicular provocative maneuvers (scalene pressure or positive Tinel sign over scalenes); (3) upper or lower trunk symptoms that worsen with infraclavicular provocative maneuvers (positive Tinel sign medial to coracoid or tenderness to palpation over the coracoid process); (4) reproduction of pain with 90° of abduction in external rotation or upper limb tension test, and (5) participation in work/exercise requiring repetitive arm stress (overhead athletes, throwing sports, protracted posture at work, etc). Conclusion: This study proposed 5 clinical criteria for distinguishing nTOS that were agreed upon by 20 upper extremity, nerve, and vascular surgery experts. These criteria can be used to develop a future diagnostic algorithm for nTOS, allowing for further research and more efficient nTOS treatment.